Down-regulation of multiple CDK inhibitor ICK/KRP genes promotes cell proliferation, callus induction and plant regeneration in Arabidopsis - Cheng, Yan; Liu, Han; Cao, Ling; Wang, Sheng; Li, Yongpeng; Zhang, Yuanyuan; Jiang, Wei; Zhou, Yongming; Wang, Hong (Frontiers in Plant Science, 2015)
The ICK/KRP cyclin-dependent kinase (CDK) inhibitors are important plant cell cycle regulators sharing only limited similarity with the metazoan CIP/KIP family of CDK inhibitors. Information is still limited regarding the specific functions of different ICK/KRP genes in planta. We have shown previously that down-regulation of multiple CDK inhibitor ICK/KRP genes up-regulates the E2F pathway and increases cell proliferation, and organ and seed sizes in Arabidopsis. In this study, we observed that the quintuple ick1/2/5/6/7 mutant had more cells in the cortical layer of the root apical meristem than the wild type while its root apical meristem length was similar to that of the wild type, suggesting a faster cell cycle rate in the quintuple mutant. We further investigated the effects of down-regulating ICK genes on tissue culture responses. The cotyledon explants of ick1/2/5/6/7 could form callus efficiently in the absence of cytokinin and also required a lower concentration of 2,4-D for callus induction compared to the wild type plants, suggesting increased competence for callus induction in the mutant. In addition, the quintuple ick mutant showed enhanced abilities to regenerate shoots and roots, suggesting that increased competence to enter the cell cycle in the quintuple mutant might make it possible for more cells to become proliferative and be utilized to form shoots or roots. These findings indicate that CDK activity is a major factor underlying callus induction and increased cell proliferation can enhance in vitro organogenesis.